On prorated servicing costs for two-dimensional warranties with combined repair-replacement strategies. (4th November 2010) - Jayaraman, Raja; Matis, Timothy I.
We study a non-renewing two-dimensional warranty policy for repairable products with pro-rated cost for rectifying failures within a warranty coverage period defined by a rectangular region. Product failures in different warranty regions have different cost implications based on repair-replacement strategy employed by the manufacturer and the time and usage at the event of product failure. We obtain expressions for expected cost to the manufacturer based on two possible repair-replacement strategies which can be employed towards servicing the product in the event of failures and present the respective costs associated with them.